Growth and lipid accumulation of microalgae from fluctuating brackish and sea water locations in South East Queensland—Australia - Duong, Van Thang; Thomas-Hall, Skye R.; Schenk, Peer M. (Frontiers in Plant Science, 2015)
One challenge constraining the use of microalgae in the food and biofuels industry is growth and lipid accumulation. Microalgae with high growth characteristics are more likely to originate from the local environment. However, to be commercially effective, in addition to high growth microalgae must also have high lipid productivities and contain the desired fatty acids for their intended use. We isolated microalgae from intertidal locations in South East Queensland, Australia with adverse or fluctuating conditions, as these may harbor more opportunistic strains with high lipid accumulation potential. Screening was based on a standard protocol using growth rate and lipid accumulation as well as prioritizing fatty acid profiles suitable for biodiesel or nutraceuticals. Using these criteria, an initial selection of over 50 local microalgae strains from brackish and sea water was reduced to 16 strains considered suitable for further investigation. Among these 16 strains, the ones most likely to be effective for biodiesel feedstock were Nitzschia sp. CP3a, Tetraselmis sp. M8, Cymbella sp. CP2b and Cylindrotheca closterium SI1c, reaching growth rates of up to 0.53 day-1 and lipid productivities of 5.62 µg mL-1day-1. Omega-3 fatty acids were found in some strains such as Nitzschia sp. CP2a, Nitzschia sp. CP3a and Cylindrotheca closterium SI1c. These strains have potential for further research as commercial food supplements.